2021
DOI: 10.3389/fcell.2021.684398
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Attenuates Chromium (VI)-Induced Spermatogonial Stem Cell/Progenitor Mitophagy by Restoration of METTL3-Mediated RNA N6-Methyladenosine Modification

Abstract: Spermatogonial stem cells (SSCs) are the basis of spermatogenesis, and any damage to SSCs may result in spermatogenic disorder and male infertility. Chromium (Cr) (VI) is a proven toxin, mutagen, and carcinogen, perpetually detrimental to environmental organisms due to its intricate and enduring detoxification process in vivo. Despite this, the deleterious effects of Cr (VI) on SSCs and the underlying mechanisms remain poorly understood. In this study, we identified that Cr (VI) impaired male reproductive syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…In addition, in the presence of cadmium sulfate-induced oxidative damage, FTO expression decreases, the m6A modification of the long noncoding RNAs (lncRNAs) lncRNA-MALAT1 and lncRNA-PVT1 increases, and the expression levels of lncRNA-MALAT1 and lncRNA-PVT1 decrease, which in turn induces biological activities, such as ROS accumulation, malondialdehyde (MDA) accumulation and decreased superoxide dismutase (SOD) activity (Qu et al, 2021). Chromium (Cr) (VI) is a toxic substance, and Lv et al (2021) found that Cr(VI) can cause mitochondrial damage in spermatogonial stem cells/progenitors, resulting in increased FIGURE 2 | AS risk factors involved in the regulation of m6A methylation-related target genes; the picture was created with BioRender. The genes associated with oxidative stress and m6A RNA modification include HECTD4, ABCA5, SLC22A17, KCNQ5, lncRNA-MALAT1, and lncRNA-PVT1; genes associated with obesity and m6A RNA modification include SRSF2 and PPAR-γ; and genes associated with smoking and m6A modification include ZBTB4, EZH2 and H3K27me3.…”
Section: M6a Ribonucleic Acid Modification and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the presence of cadmium sulfate-induced oxidative damage, FTO expression decreases, the m6A modification of the long noncoding RNAs (lncRNAs) lncRNA-MALAT1 and lncRNA-PVT1 increases, and the expression levels of lncRNA-MALAT1 and lncRNA-PVT1 decrease, which in turn induces biological activities, such as ROS accumulation, malondialdehyde (MDA) accumulation and decreased superoxide dismutase (SOD) activity (Qu et al, 2021). Chromium (Cr) (VI) is a toxic substance, and Lv et al (2021) found that Cr(VI) can cause mitochondrial damage in spermatogonial stem cells/progenitors, resulting in increased FIGURE 2 | AS risk factors involved in the regulation of m6A methylation-related target genes; the picture was created with BioRender. The genes associated with oxidative stress and m6A RNA modification include HECTD4, ABCA5, SLC22A17, KCNQ5, lncRNA-MALAT1, and lncRNA-PVT1; genes associated with obesity and m6A RNA modification include SRSF2 and PPAR-γ; and genes associated with smoking and m6A modification include ZBTB4, EZH2 and H3K27me3.…”
Section: M6a Ribonucleic Acid Modification and Oxidative Stressmentioning
confidence: 99%
“…The authors explored the mechanism and found that the m6A RNA modification level decreased in spermatogonial stem cells/progenitors treated with Cr (VI), while melatonin restored the expression of METTL3. Cr(VI)-induced damage was reversed by restoring METTL3mediated RNA m6A modification and activating mitofusin 2 (MFN2) and optic atrophy 1 (OPA1), as well as inhibiting the Bcl-2/adenovirus E1B 19-kDa-interacting protein 3 (BNIP3)/NIX mitophagy receptor pathway (Lv et al, 2021). However, studies on the relationship between AS, epitranscriptomics, and ROS are still lacking; their relationship requires further investigation.…”
Section: M6a Ribonucleic Acid Modification and Oxidative Stressmentioning
confidence: 99%
“…Adult male C57BL/6J mice pretreated with melatonin intraperitoneal injections (25 mg/kg b.w./day × 14 days) exhibited attenuated cell viability loss, ROS generation, mitochondrial dynamics imbalance, and mitophagy in spermatogonial stem cells (SSCs) induced by daily intraperitoneal injections with chromium (VI) (16.2 mg/kg b.w./day × 14 days), an environmental toxin and carcinogen that can cause male infertility by damaging SSCs [ 1046 , 1047 , 1048 ]. In vitro mouse SSCs/progenitor cells treated with 10 μM chromium (VI) exhibited decreased METTL3 mRNA levels, but cells pretreated with 50 μM melatonin were able to attenuate the downregulation of METTL3 [ 1046 ].…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
“…Adult male C57BL/6J mice pretreated with melatonin intraperitoneal injections (25 mg/kg b.w./day × 14 days) exhibited attenuated cell viability loss, ROS generation, mitochondrial dynamics imbalance, and mitophagy in spermatogonial stem cells (SSCs) induced by daily intraperitoneal injections with chromium (VI) (16.2 mg/kg b.w./day × 14 days), an environmental toxin and carcinogen that can cause male infertility by damaging SSCs [ 1046 , 1047 , 1048 ]. In vitro mouse SSCs/progenitor cells treated with 10 μM chromium (VI) exhibited decreased METTL3 mRNA levels, but cells pretreated with 50 μM melatonin were able to attenuate the downregulation of METTL3 [ 1046 ]. An interesting observation was the significant elevation of METTL3 to levels above controls in the melatonin-only samples, whereas YTHDF2 levels were significantly elevated above the control samples in the melatonin + chromium (VI) cells after 4 h, which again supports the theory that the expression of YTHDF2 may be correlated with stress levels [ 1016 ], and can be increased by the presence of melatonin, and perhaps other antioxidants [ 1045 ].…”
Section: Melatonin May Attenuate the Stress-induced Aggregation Of Pathological Mlos Via Post-translational Modification And Rna Modificamentioning
confidence: 99%
“…METTL3-mediated RNA m6A modification and activation of mitochondrial fusion proteins MFN2 and OPA1, as well as inhibition of the mitophagy BNIP3/NIX receptor pathway, restored mitochondrial function. ALKBH1-deficient HEK293 cells showed increased mtDNA copy numbers and mitochondrial dysfunction ( Lv et al, 2021 ). Meanwhile, Du et al found that the expression of m6A demethylase FTO was decreased during ischemia–reperfusion injury.…”
Section: N6-methyladenosine Facilitates Mitochondrial Dysfunctionmentioning
confidence: 99%